THE RELATIONSHIP OF EMERGENCY INSTALLATION SERVICE RESPONSE TIME WITH PATIENT SATISFACTION AT SPECIALIZED HOSPITAL DUREN SAWIT, EAST JAKARTA IN 2023 - Suyatno, Suyatno; Kusnanto, Kusnanto (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Background: The number of patient visits to the Emergency Room (ER) has increased by around 30%. Based on statistical data from NHS England (2018) in the United Kingdom (2018), the number of patient visits to the ER is estimated to be more than 23,7 million. In 2019, the number of patients treated in the ER in Korea was 10.609.107, while in Indonesia the number of visits to the ER was 4,402,205 patients (13,3%). In DKI Jakarta in 2022 the number of emergency room visits will be 72%. The emergency room must be able to provide fast and appropriate assistance for patient safety, namely by providing a response time of ≤ 5 minutes. One of the determining indicators of patient satisfaction and the quality of health services in the emergency department is response time. Purpose: Knowing the relationship between emergency unit service response time and patient satisfaction levels. Methods: Analytical with cross sectional design. The sample in this study was a portion of the emergency room patients at Specialized Hospital Duren Sawit, East Jakarta in December 2023, totaling 75 people. The sampling technique uses Random Sampling. Results: Frequency distribution of emergency room patient satisfaction, most respondents said they were satisfied (69,3%) and the response time for emergency department services was mostly fast (52,0%). There is a relationship between the response time of emergency department services and the level of patient satisfaction (p value 0,000). Conclusion: There is a relationship between the response time of emergency department services and the level of patient satisfaction. It is hoped that health workers on duty in the emergency room can improve services in accordance with hospital standards to increase patient satisfaction.